Trunk extensor fatigue decreases jump height similarly under stable and unstable conditions with experienced jumpers - Howard, J.; Granacher, U.; Behm, D. G. (European Journal of Applied Physiology, 2015)
Purpose: The purpose of this study was to investigate the effects of back extensor fatigue on performance measures and electromyographic (EMG) activity of leg and trunk muscles during jumping on stable and unstable surfaces.